Shrimp Post-Larvae Nursing in Earthen Ponds, Bangladesh - Jannat, M.; Ahmed, M. K.; Islam, M. M.; Kundu, G. K.; Kamruzzaman, M. (Journal of Scientific Research, 2017)
In Bangladesh, shrimp post-larvae (PL) are mainly produced in hatcheries. From 2000s shrimp PL are reared in nurseries containing small earthen ponds by relatively poor people for a few days before stocking into the shrimp farms. This study assesses the physical and chemical parameters of five such nurseries at Satkhira district, Bangladesh using scientific instruments and semi-structured questionnaire. The nursing process involved stocking of PL (4151.8 ± 1581.35 PL/m2) in small earthen ponds (<18m2 area/pond) and raring for up to 10 days with feeding. Most of the physico-chemical parameters were within the suitable range recommended for shrimp culture. The survival rate of PL ranged from 80% to 90%. The nursing system was profitable as the average Benefit-Cost Ratio (BCR) was 1.19. The establishment and operation of these nurseries do not require any expensive equipment or complex technology and can be run by less educated and poor people. However, constraints like lack of credit and continuous water supply are hindering the scaling up of these nurseries in size and number. By providing means to overcome the constraints these nurseries can be an excellent income generating source for the poor entrepreneurs as well as contribute in increasing shrimp production in Bangladesh.